Genetic and rat toxicity studies of cyclodextrin glucanotransferase. (2016) - Maronpot, Robert R.; Hobbs, Cheryl A.; Davis, Jeffrey; Swartz, Carol; Boyle, Molly; Koyanagi, Mihoko; Hayashi, Shim-mo
Highlights: Bacterial cyclodextrin glucanotransferase (CGTase) is used to produce a water soluble form of glycosylated isoquercitrin. Genotoxicity battery on CGTase and sodium sulfate negative for mutations and DNA damage. No evidence of systemic toxicity in 90-day rat toxicity study of CGTase. Abstract: Introduction: Microbiologically derived cyclodextrin glucanotransferase (CGTase) is used commercially as a processing agent in manufacture of food, pharmaceuticals, and cosmetics. Its toxic potential was evaluated in anticipation of use in the production of alpha -glycosyl isoquercitrin, a water-soluble form of quercetin. Methods: Following OECD guidelines, CGTase, produced by Bacillus pseudalcaliphilus DK-1139, was evaluated in a genotoxicity battery consisting of a bacterial reverse mutation assay, an in vitro micronucleus (MN) assay and MN and comet assays using B6C3F1 male and female mice. These same genotoxicity assays were also conducted for sodium sulfate, a contaminant of CGTase preparation. In a 90-day Sprague Dawley rat toxicity study, CGTase was administered by gavage in water at daily doses of 0, 250, 500, and 1000 mg/kg/day. Results: CGTase did not induce mutations with or without metabolic activation in the bacterial reverse mutation assay. Formation of micronuclei was not induced in either in vitro or in vivo MN assays with or without metabolic activation. No induction of DNA damage was detected in male or female mouse liver, stomach, or duodenum in the comet assay. Sodium sulfate also tested negative in these same genotoxicity assays. In the 90-day repeated dose rat study there were no treatment-related adverse clinical or pathological findings. Conclusion: The genotoxicity assays and repeated dose toxicity study support the safe use of CGTase in production of alpha -glycosyl isoquercitrin.